ANALISIS SIKAP DAN MINAT BELAJAR SISWA KELAS XI IPA DI SMA NEGRI 15 SEMARANG TERHADAP MATA PELAJARAN KIMIA - Aisyiyah Dinnur Utami; Eny Winaryati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The purpose of this research is to know the measures and the behaviour of students and the lack of interest in of students to study a class of XI at the senior high school 15 Semarang the capital city of against learning to promote disorder to chemical .Was used in the study a method of descriptive of quantitative .The collection of data in the manner of a triangulation of pt pgn promised to supply kuisoner , observation , and conducting interviews .The research sample over the withdrawal of funds there were a total of 57 respondents in the present study.The findings of this glory if it is found of the study are: 1 ) an attitude and activity of student of class XI at the senior high school  15 semarang the capital city of against learning to promote disorder to chemical, 2 ) the activity itself to of students to study in also had an impact indirect positive impact on the lack of interest in of students to study a class of XI at the senior high school n 15 semarang the capital city of against learning to promote disorder to chemical.Keyword :Research, students attitude, interest students, chemical.